Exchange Rate Analysis: Short-Term and Long-Term Balance - Handayani, Khoriro; Santosa, Budi (International Journal of Law Policy and Governance, 2022)
This study aims to analyse how the impact of inflation, money supply, and export to influence the movement of the IDR/USD exchange rate, so it is expected to be used as a basis for determining reduction policy to mountain the IDR/USD exchange rate. The method of analyse used this research is linier regression data time series with Error Correction Model (ECM) analysis method with the help of software E-views 9. The data used in this study are secondary data obtained from IFS and BI. The results of the study show that in the short and long term, inflation and money supply have a positive effect and exports have a negative effect on the IDR/USD exchange rate.